Triagem auditiva em lactentes com indicadores de risco para deficiência auditiva: comparação entre ambiente hospitalar e ambulatorial - Rosa, Barbara Cristina da Silva (2011)
Introduction: The Universal newborn hearing screening (UNHS) was not implemented in most of Brazilian hospitals yet. Therefore, one option is to perform the evaluation gradually, in newborns and risk infants in the hospital as inpatients, and with an outpatient approach. Goal: To compare the results of selective hearing screening in two different approaches: outpatient and inpatient, in an infant population with risk indicators for hearing loss. Method: It was analyzed two databases, the first one with the results of extenso in a maternity with 284 newborns and infants, and the second one, a database of an university audiological clinic with 398 newborns and infants. The following variables were analyzed: extensor according to the Brazilian multiprofessional health hearing committee and the ones applied by the Secretary of Health in São Paulo city; age in extenso and hearing diagnosis, access during the screening process, return for re-screening and diagnosis. Results: At the university clinic the most prevalent risks indicators for hearing loss were: NICU for more than five days (48%) and use of ototoxic drugs (19,8%). In the maternity the most prevalent risks were: low for gestational age (40,5%) family hearing loss (19%). Concerning the access at the clinic for the retest, it was observed 78,20% and for the diagnosis 73,3%. In the maternity the access was 100%, for retest and for the hearing diagnosis. When applied the risk indicators from the Brazilian Hearing committee in the maternity, only 167 newborns were considered as risk babies. Conclusion: When the HDRI were applied according to Multiprofessional health hearing committee, the numbers of infants that would perform the screening decreased and the prevalence of hearing loss increased. In the adhesion process, it was verified that both in the hospital in the retest of hearing screening, and audiological diagnosis was of 100%